DATASET_GHANA_FISH EPIDEMIOLOGY AND HEALTH ECONOMICS SURVEY - Khor, Laura (2025)
The dataset titled "Ghana Fish Epidemiology and Health Economics Survey" focuses on the intersection of fish health and economic factors in Ghana. This survey aimed to collect data on fish farm inputs/outputs that could lead to emerging diseases and economic losses.